The vision of bedfast nursing home residents of their quality of life and the contribution of technological innovations in and around the bed. Issue 2 (18th June 2018) - Martens, I.; Verbeek, H.; Aarts, J.; Bosems, W.P.H.; Felix, E.; van Hoof, J.
Abstract : Purpose: Over 8 per cent of the Dutch nursing home population is bedfast, and this number is slowly increasing. The quality of life (QoL) of this population is lower than that of residents who are still mobile. Little research has been conducted on how to improve the QoL of this bedfast population, particularly through making technological adjustments to the bed and the direct surroundings. The purpose of this paper is to gain insight into the QoL of bedfast residents and how to improve this through technology. Design/methodology/approach: A mixed-method multi-case study with thematic analysis was conducted in two nursing homes with seven participants based on semi-structured interviews and Short Form-12 questionnaire. Findings: The major causes of the experienced low QoL were the limited opportunities for engaging in social contacts with others, and coping with the dependency on other people and having limited control. Participants suggested improvements of QoL through the application of modern communication technologies to engage in social contacts and to control the bed itself and environment around the bed. Practical implications: The results may help improve the design of the bed and the direct environment in order to improve the QoL of bedfast nursing home residents. Originality/value: The QoL of bedfast nursing home residents has not been studied before in relation to the bed itself and technological solutions that may help improve the QoL and level of control.